Comment on 'Germanium electron–hole bilayer tunnel field-effect transistors with a symmetrically arranged double gate'. (26th October 2015) - Padilla, J L; Alper, C; Gámiz, F; Ionescu, A M
Abstract: In this comment we demonstrate that the inclusion of field-induced quantum confinement effects through appropriate discretization of conduction and valence bands refutes the suitability of a germanium electron–hole bilayer tunnel field-effect transistor with symmetrically arranged gates (Jeong et al 2015 Semicond. Sci. Technol. 30 035021 ). Delayed alignment of the first electron and hole energy subbands in the central gated intrinsic channel region makes the onset of vertical band-to-band tunneling unattainable at low applied voltages for the metal workfunctions used by Jeong et al . Furthermore, quantization effects lead to the appearance of unavoidable parasitic lateral tunneling to the lightly doped drain-source region (LDD), which seriously degrades the switching behavior reported by Jeong et al .